Media Literacy Education: development, aproaches and challenges in an interconnected world (Foro de Educacion, 2012)
The Media Literacy Education is a theoretical and practical field of study that connects two disciplines: education and communication. After the interest and initial impetus in the 70 and 80, the Media Literacy Education becomes a heterogeneous and plural field of study. Therefore, after a short historical overview of the most significant underlying points, we will present the latest definitions and the characteristics of the two main approaches. Once we have contextualized this matter we will investigate the dialogical character of a real Media Literacy Education. At this point, we do a personal proposal about how to understand this discipline and its true nature. Finally, we will study the current challenges that Media Literacy Education must pay attention in an interconnected world.